Real time image and voice processing input for online multiplayer computer games - Waliullah, Syed Shaiyan Kamran (BRAC University, 2013)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2012.